2022
DOI: 10.7759/cureus.25410
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Laboratory Findings Associated With Diabetic Ketoacidosis in Hospitalized Pediatric Patients

Abstract: Background: Diabetic ketoacidosis (DKA), the most serious and acute complication of type 1 diabetes, has an incidence of 6%-8% among known pediatric type 1 diabetes patients, although risk factors associated with severe DKA in the pediatric population are poorly understood [ 1 ]. Method: A single-institution, retrospective chart analysis of pediatric DKA patients admitted to our pediatric intensive care unit (PICU) was conducted in South Alabama between October 2017 and April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Markers of oxidative stress (WBC, platelets, and MPV) were associated with increased severity of DKA. Sehgal M. et al (22) reported that both leukocytosis and thrombocytosis were associated with severe metabolic acidosis. Karavanaki K. et al (23) reported a significantly higher WBC value in patients with moderate or severe DKA compared to those with mild DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of oxidative stress (WBC, platelets, and MPV) were associated with increased severity of DKA. Sehgal M. et al (22) reported that both leukocytosis and thrombocytosis were associated with severe metabolic acidosis. Karavanaki K. et al (23) reported a significantly higher WBC value in patients with moderate or severe DKA compared to those with mild DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Важную роль в патофизиологии ОС играет именно окислительная модификация белков, чья роль в клеточном повреждении гораздо более значима, чем при перекисном окислении липидов, особенно при ДКА [40]. С другой стороны, ОС, вызванный ДКА, способствует дисфункции β-клеток поджелудочной железы, которые индуцируют высвобождение гормонов, противодействующих инсулину (глюкагон, кортизол и гормон роста), что приводит к активации печеночного глюконеогенеза и еще более выраженной гипергликемии (т.е., по сути, усилению клинических проявлений ДКА) [41]. Повышенный липолиз на фоне ОС ускоряет доставку СЖК в печень для синтеза кетоновых тел: ацетоацетата и β-гидроксибутирата, что приводит к метаболическому ацидозу, по сути формируя синдром порочного круга [42].…”
Section: дка и ос: синдром порочного круга?unclassified
“…ДКА, запуская процессы ОС, стимулирует выработку митохондриальных активных форм кислорода (АФК), что вызывает внутриклеточный ОС и последующую резистентность к инсулину [34,38]. С другой стороны, ОС, вызванный ДКА, вызывает дисфункцию β-клеток поджелудочной железы, которые индуцируют высвобождение гормонов, противодействующих инсулину (глюкагон, кортизол и гормон роста), что приводит к усилению печеночного глюконеогенеза и еще более выраженной гипергликемии (по сути, усилению клинических проявлений ДКА) [39]. ОС и образование АФК могут приводить к пертурбации капилляров и клеточному повреждению липидов, мембран, белков и ДНК [15].…”
Section: оксидативный стрессunclassified